Global Trends of Islam and Science Research: A Bibliometric Analysis from 2014 to 2023 and the Integration in Learning - Zulfah, Zulfah; Faisal, Muhammad (Al Asma: Journal of Islamic Education, 2025)
Islam and science have had a long history and a relationship that often supports and influences each other. This research aims to study global trends in publications related to Islam and science from 2013 to 2024, which can be considered in implementing learning. Islamic and scientific research uses Biblioshiny and Vosviewer analysis to understand global trends thoroughly. Documents were taken from Scopus data with a total of 2685 which were then filtered into 323 documents using the prism method. The results of Biblioshiny's analysis show the distribution of articles per year, journal sources that publish a lot, affiliations and countries that write a lot. The results of the Vosviewer analysis in the overlay visualization show that topics related to systematic reviews, meta-analysis, and integration are the current topics carried out by researchers. Meanwhile,   the topics of Islam, science, religion, and roles are often researched, while topics related to systematic reviews, meta-analysis, and integration, apart from being current topics, are also research topics that people rarely do, so they have the potential to continue to be developedThe topic of integration, which has not been widely discussed, can inspire teachers and lecturers to combine Islam and science in their classroom lessons. This approach can help students recognize that Islam sees science as a way to understand the signs of God's greatness in the universe.